Student involvement in assessment: learning experiences for behavior change - Ratnawati Susanto (Pedagonal : Jurnal Ilmiah Pendidikan, 2022)
The purpose of this study was to obtain data on the situation of learning experiences carried out by teachers in changing student learning behavior by involving students in assessment. The research method used is a qualitative survey method and uses a 5-choice questionnaire that was built and developed from the student assessment concept of David M. Johnson, with a population of primary school teachers in West Jakarta totaling 100 teachers. The research findings provide information that the structure of the learning experience carried out by the teacher to help student behavior learning outcomes through student assessments is in a condition that is not yet effective and a basic literacy assessment model needs to be developed.The conclusion of the study shows that the teacher's ability to condition student involvement in assessment as a learning experience for behavioral change is effective in aspects of academic learning and the focus of assessment.